PERKEMBANGAN PESANTREN DI KOMUNITAS ISLAM MODERN UNTUK MENINGKATKAN KUALITAS PENDIDIKAN ISLAM: STUDI ATAS PESANTREN MUHAMMADIYAH - Muhammad Awwaludin Aprilianto; Iksan Kamil Sahri (Sekolah Tinggi Agama Islam Negeri (STAIN) Teungku Dirundeng Meulaboh Aceh Barat, 2025)
This research aims to reveal the Islamic education system in Muhammadiyah which is famous for its motto of Progressive Islam, so that a modernization of education movement is formed to improve the quality of Islamic education. As one of Muhammadiyah's programs is to carry out a tajdid or reform movement. One thing that is starting to develop rapidly at this time in Muhammadiyah is the Modern Islamic Boarding School with the integration of religious knowledge with general knowledge. This research uses a qualitative approach-literature study and uses documentation methods to collect data. The results of this research are to explain the dynamics of Muhammadiyah education and the development of modern Muhammadiyah Islamic boarding schools. The Muhammadiyah education reform movement has existed since its inception, with the aim of producing intellectual scholars and religious scholars. One of the Muhammadiyah movements that is currently developing rapidly is the Islamic boarding school with a modernist system which consists of three, namely: Muhammadiyah Boarding School (MBS), Integral Islamic boarding school, and Takhassus Islamic boarding school